Effects of antiarrhythmics on atrial high rate episodes and progression to clinical atrial fibrillation (ANTI-AHRE) - Simovic, S; Taleski J; Todorovic, Z; Kircanski, B (Oxford University Press (OUP), 2023)
Abstract Funding Acknowledgements Type of funding sources: None. Background Atrial High Rates Episodes (AHRE) are associated with progression to clinical atrial fibrillation (AF), stroke, increased risk of MACE and increased mortality (1-4). Although oral anticoagulation should be initiated in patients with CHADs-VASc score ≥ 2 and episode duration ≥ 24h, treatment of AHRE with antiarrhythmics was not investigated so far. Purpose This study aimed to assess the effects of antiarrhythmic treatment on AHRE and its impact on the progression to clinical AF and AHRE burden. Methods This study included patients with AHRE duration ≥ 24h detected by dual-chamber pacemakers, without a previous diagnosis of AF and treatment with antiarrhythmics. Nominal settings with high atrial rate criterion programmed to 200 beats/min were used for AHRE detection. Patients were randomized to the Intervention (n=169) and Control Group (n=138). Patients in the Intervention Group received antiarrhythmic treatment (Ic antiarrhythmics (n=54), beta-blockers (n=58) and amiodarone (n=57)). The primary endpoint was progression to clinical AF and the secondary endpoint was AHRE burden. Results A total of 307 were included in the study, with a mean age of 71.4±8.15, 166 (54.07%) females and a mean follow-up 20.84±5.04 months. The baseline characteristics did not differ significantly between groups. During the follow-up, 50 patients (36.23%) from the Control group developed clinical AF. In groups of patients treated with Ic antiarrhythmics, beta-blockers and amiodarone, clinical AF developed in 11 (20.37%), 25 (25.86%) and 5 (8.77%) patients, respectively (p<0.001). Average time to clinical AF progression was significantly longer in groups of patients treated with antiarrhythmics (Ic antiarrhythmics, beta-blockers and amiodarone) compared to the Control group (17.7, 17.2, 19.0 vs 15.9 months, respectively, p<0.001). The Kaplan-Meier plot of freedom from clinical AF is given in Figure 1. Amiodarone prolonged the time to clinical AF progression significantly compared to beta-blockers (p=0.017), while a trend was observed compared to Ic antiarrhythmics (p=0.057). No significant differences between Ic antiarrhythmics and beta-blockers were observed in time to clinical AF progression (p=0.567). The AHRE burden was significantly lower in the Intervention group compared to the Control group (6.9% vs 15.4%, p<0.001). Amiodarone was superior in lowering the AHRE burden when compared to Ic antiarrhythmics and beta-blockers (2.1% vs 5.6% and 7.8%, respectively, p<0.001), while no significant differences were observed between Ic antiarrhythmics and beta-blockers (p=0.18) Conclusion Initiating antiarrhythmics for AHRE episodes leads to a lower AHRE burden and progression to clinical AF. Randomized clinical trials are needed to investigate further the early antiarrhythmic treatment of AHRE without clinical AF.